Efektivitas Bible Camp terhadap Pembinaan Iman Kristen para Pemuda - Yerliani Boymau; Hendrik A. E. Lao (JUITAK: Jurnal Ilmiah Teologi dan Pendidikan Kristen, 2025)
Youth represent a socio-psycho-spiritual entity undergoing a critical transitional phase, characterized by identity crises, value disorientation, and pressures from secular-cultural influences. Within the framework of Christian pastoral theology and pedagogy, faith formation serves as a strategic mechanism to cultivate integrative spiritual maturity, encompassing cognitive (doctrinal understanding), affective (spiritual affection), and conative (practical orientation) dimensions. This study analyzes the effectiveness of Bible Camp as an experiential learning-based faith formation model in the spiritual development of youth. Employing a qualitative descriptive approach through participatory observation, in-depth interviews, and document analysis, the research explores the contribution of Bible Camp to the internalization of theological values, the construction of religious identity, and the strengthening of faith community cohesion. The findings indicate that Bible Camp activities—such as hermeneutic study, collective worship, existential reflection, and group dynamics—result in significant faith transformation on both personal and communal levels. This process aligns with Streib’s faith development theory and Mezirow’s transformative learning theory, which emphasize cognitive reconstruction through reflective experience within a social context. Bible Camp effectively mediates the transition from conventional faith to reflective and dialogical faith, while enhancing youth’s spiritual competencies in confronting the complexities of contemporary reality. The findings reinforce the assumption that faith formation in interactive non-formal settings is more effective than conventional instructional approaches in producing theological and ethical paradigm shifts. Therefore, Bible Camp is positioned as a relevant and contextual ecclesiological instrument in the recontextualization of Christian faith education. This model functions not only as a venue for individual spiritualization but also as a catalyst for the formation of resilient, participatory, and transformative Christian character within a pluralistic socio-religious ecosystem. Recommendations are directed towards institutionalizing Bible Camp as a systemic strategy for youth faith formation in the mission of the contemporary church.